The Influence Of Profitability And Capital Structure On Company Value In Coal Sub-Sector Mining Companies Registered In Idx For The 2014-2017 - Muhammad Yasin; Pramita Studiviany S (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of profitability, liquidity, and capital structure on firm value in coal mining companies listed on the Indonesian stock exchange for the 2014-2017 period. The total population in this study amounted to 21 coal mining companies and after selecting samples using purposive sampling technique, it was obtained 8 companies that will be used as samples in this study . The results showed that capital structure had a negative effect on firm value, profitability had a positive effect on firm value. Meanwhile, the simultaneous results of profitability and capital structure have a significant effect on firm value. The magnitude of the ability of independent variables (profitability, and capital structure) in explaining the variable dependent (the value of the company) is at 85.7% while the remaining 14.3% is determined by other variables not examined in the study of this.